Digital broadcasting : an introduction to new media - Pierson, Jo (Berg new media series., 2015)
"Digital Broadcasting presents an introduction to how the classic notion of 'broadcasting' has evolved and is being reinterpreted in an age of digitization and convergence. The book argues that 'digital broadcasting' is not a contradiction in terms, but-on the contrary-both terms presuppose and need each other. Drawing upon an interdisciplinary and international field of research and theory, it looks at current developments in television and radio broadcasting on the level of regulation and policy, industries and economics, production and content, and audience and consumption practices"--